A CTAB-assisted morphology-controlled copper-doped few-layer MoS2 photothermal catalyst, its preparation method, and its application.

CN122937825APending Publication Date: 2026-10-20NORTHWEST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611347531.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有报道中,CTAB等表面活性剂虽被用于调控MoS2形貌,但尚未见将其与Cu掺杂及缺陷工程相结合,并应用于光热RWGS反应的技术方案

Benefits of technology

1、CTAB作为形貌导向剂可显著降低MoS2层数。TEM结果显示,未添加CTAB的多层MoS2约为6~8层,而CTAB辅助得到的Cu-FL-MoS2主要为2~4层,有利于增加可利用的表面和缺陷位点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a CTAB-assisted morphology-controlled copper-doped few-layer MoS2 photothermal catalyst, its preparation method, and its application in a photothermal reverse water-gas shift reaction. Using ammonium molybdate tetrahydrate and thioacetamide as molybdenum and sulfur sources, respectively, cetyltrimethylammonium bromide (CTAB) and copper acetate are added to the aqueous phase. The pH of the reaction system is controlled, and the mixture undergoes hydrothermal reaction at 180 °C, washing, drying, and calcination under nitrogen atmosphere to obtain copper-doped few-layer 2H-MoS2 containing sulfur vacancies. CTAB can control the number and morphology of MoS2 layers. Copper species are predominantly in low-valence states and synergistically interact with sulfur vacancies, thereby improving carrier separation, light absorption, and CO2 adsorption activation. A sample with a preferred Cu:Mo molar ratio of 15% exhibits a CO generation rate of 160.0 μmol·g under full-spectrum irradiation with a 300 W xenon lamp, at 180 °C, and a CO2:H2 volume ratio of 1:1. ‑1 ·h ‑1 It exhibits a CO selectivity of 99.0% and good cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photothermal catalytic carbon dioxide hydrogenation technology, specifically to a copper-doped few-layer MoS2 photothermal catalyst prepared using a hexadecyltrimethylammonium bromide (CTAB) assisted solution-directed strategy, its preparation method, and the application of the catalyst in the photothermal reverse water-gas shift reaction (RWGS, CO2+H2→CO+H2O). Background Technology

[0002] The massive emission of carbon dioxide (CO2) has become a global environmental concern. Catalytically converting CO2 into high-value-added chemicals is a crucial pathway to achieving carbon reduction and resource utilization. The reverse water-gas shift reaction (RWGS, CO2 + H2 → CO + H2O) can convert CO2 and green hydrogen into CO. This product can serve as a key raw material for downstream chemical processes such as Fischer-Tropsch synthesis and methanol synthesis, thus possessing significant application value in the C1 chemical industry.

[0003] Currently, research on RWGS reactions mainly focuses on thermocatalysis. While traditional thermocatalysts (such as supported noble metals Pt and Pd, and transition metals Cu and Ni) exhibit certain catalytic activity, they typically require high temperatures (>300℃) to achieve ideal CO yields. These high temperatures not only lead to energy consumption issues but also easily cause metal sintering and carbon deposition deactivation, limiting the long-term stability of the catalysts. In recent years, photothermal catalysis technology has attracted widespread attention due to its ability to couple photoexcitation and thermal effects, driving the CO2 hydrogenation reaction under mild conditions. Photothermal catalysts can utilize the thermal effect generated by light to increase the catalyst surface temperature, while photogenerated charge carriers can participate in the reactant activation process, thereby achieving higher reaction rates under lower external heating conditions.

[0004] Molybdenum disulfide (MoS2), a typical two-dimensional transition metal sulfide, possesses a tunable band structure, a wide light absorption range, and abundant edge active sites, demonstrating its application potential in photocatalysis and photothermal catalysis. Studies have shown that the activity of MoS2-based catalysts is closely related to the number of layers and defect structure. In multilayer MoS2 (>5 layers), due to strong interlayer van der Waals forces, active sites are mainly exposed at the edges, while basal sites are difficult to fully utilize. Simultaneously, interlayer stacking inhibits the separation and transport of photogenerated carriers, leading to limited catalytic efficiency. Furthermore, sulfur vacancies in MoS2, acting as defect active centers, can affect the adsorption and activation behavior of reactants. However, how to systematically control the number of layers in MoS2 to expose more active sites, while simultaneously effectively constructing and utilizing sulfur vacancies, remains a challenge for applying this material in RWGS reactions.

[0005] Copper-based catalysts have been extensively studied in RWGS reactions due to their high CO selectivity and low tendency for side reactions. Introducing copper species into the MoS2 system can theoretically modulate the electronic structure of MoS2 and construct new active interfaces. Existing literature reports the CO2 hydrogenation performance of Cu / MoS2 composites; for example, Cu-doped MoS2 prepared by hydrothermal or impregnation methods can catalyze CO2 reduction under photothermal conditions. However, current methods of introducing Cu often lack synergistic control over the number of MoS2 bulk layers and defect structures. On the one hand, if MoS2 still exists in a multilayer stacked form, the effective contact between Cu species and the MoS2 basal surface is limited; on the other hand, if the concentration and distribution of sulfur vacancies do not match the chemical state of the Cu species, it is difficult to form efficient synergistic catalytic centers. Therefore, how to introduce Cu species while reducing the number of MoS2 layers and simultaneously modulate sulfur vacancy defects to fully utilize the synergistic effect between Cu species and sulfur vacancies is a key technical problem for improving RWGS reaction performance.

[0006] To address the aforementioned issues, no systematic preparation scheme has yet been proposed in this field that can simultaneously achieve morphology control of few-layer MoS2, Cu doping, and sulfur vacancy construction. While surfactants such as CTAB have been reported to be used to control MoS2 morphology, no technical solution has been found to combine them with Cu doping and defect engineering for application in photothermal RWGS reactions. Therefore, developing a photothermal catalyst that can efficiently catalyze RWGS reactions under mild conditions and possesses good stability is of significant research importance and application potential. Summary of the Invention

[0007] The purpose of this invention is to provide a copper-doped few-layer MoS2 photothermal catalyst with CTAB-assisted morphology regulation. The catalyst reduces the number of MoS2 layers through the guiding effect of CTAB solution and improves the separation and migration ability of photogenerated carriers and the CO2 adsorption and activation ability by utilizing the synergistic effect of Cu species and sulfur vacancies.

[0008] Another objective of this invention is to provide a method for preparing the above-mentioned catalyst, which achieves the synergistic construction of few-layer 2H-MoS2, low-valence Cu species and sulfur vacancies through pH control, CTAB-assisted hydrothermal reaction and nitrogen atmosphere calcination.

[0009] Another object of the present invention is to provide the application of the above-mentioned catalyst in the photothermal reverse water gas shift reaction, so that CO2 can be selectively converted into CO under relatively mild temperature and full-spectrum illumination conditions.

[0010] In this invention, "ML" is an abbreviation for Multi-layer, indicating multiple layers; "ML-MoS2" represents a MoS2 support with a multi-layer structure; and "FL" is an abbreviation for Few-layer, indicating a few-layer MoS2 support used for control. The technical solution of this invention is as follows: The copper-doped few-layer MoS2 photothermal catalyst of this invention is based on 2H phase few-layer MoS2, which contains sulfur vacancies. Cu species are dispersed in the few-layer MoS2 and / or on its surface, and at least some of the Cu species are low-valence Cu. + The Cu species and the sulfur vacancy constitute a synergistic catalytically active structure.

[0011] Furthermore, the few-layer MoS2 has 2 to 4 layers, and the molar ratio of Cu to Mo is 5% to 20%.

[0012] Furthermore, the molar ratio of Cu to Mo is 15%.

[0013] The preparation method of the copper-doped few-layer MoS2 photothermal catalyst of the present invention includes the following steps: Ammonium molybdate tetrahydrate and thioacetamide were dissolved in deionized water at a mass ratio of 1:1. Hexadecyltrimethylammonium bromide and copper acetate were added, and the pH of the system was adjusted to 2-4. After mixing, the mixture was subjected to a hydrothermal reaction at 160-200℃ for 16-24 h. The hydrothermal product was washed, dried, and calcined at 350-450℃ for 1-3 h under a nitrogen atmosphere to obtain the copper-doped few-layer MoS2 photothermal catalyst. The concentration of hexadecyltrimethylammonium bromide in the reaction system was 1-5 g / L, and the molar ratio of Cu to Mo was 5%-20%.

[0014] Furthermore, the pH value of the hydrothermal reaction system is 3.

[0015] Furthermore, the hydrothermal reaction temperature is 180°C, and the hydrothermal reaction time is 20 hours.

[0016] Furthermore, the calcination temperature is 400℃ and the calcination time is 2 h.

[0017] Furthermore, the washing process involves alternating between deionized water and anhydrous ethanol, followed by centrifugation three times; the drying process involves drying at 60°C.

[0018] The application of the copper-doped few-layer MoS2 photothermal catalyst of this invention in the photothermal reverse water-gas shift reaction, under the synergistic effect of light and heating, at a reaction temperature of 140~180℃, a reaction pressure of 0.2MPa, and a CO2 to H2 volume ratio of 1:1 in the reaction gas, catalyzes the reaction of CO2 and H2 to produce CO and H2O.

[0019] Furthermore, the light source is a 300W xenon lamp full-spectrum light source.

[0020] Furthermore, the molar ratio of Cu to Mo in the copper-doped few-layer MoS2 photothermal catalyst is 15%; under the conditions of a reaction temperature of 180℃, full-spectrum irradiation by a 300W xenon lamp, and a CO2 to H2 volume ratio of 1:1, the CO formation rate is 160.0 μmol•g. -1 •h -1 The CO selectivity was 99.0%.

[0021] The present invention has the following beneficial effects: 1. CTAB, as a morphology-directing agent, can significantly reduce the number of MoS2 layers. TEM results show that multilayer MoS2 without CTAB has approximately 6-8 layers, while Cu-FL-MoS2 obtained with CTAB assistance mainly has 2-4 layers, which is beneficial for increasing the available surface area and defect sites.

[0022] 2. Under pH=3 conditions, Cu doping and CTAB guidance can be used to construct few-layer 2H-MoS2 containing sulfur vacancies. EPR, XRD, Raman spectroscopy, and elemental mapping all indicate that Cu introduction did not destroy the main MoS2 crystal phase and modulated the defect structure.

[0023] 3. Cu species exist in low valence state Cu + The 15% Cu-FL-MoS2 exhibits higher transient photocurrent and lower electrochemical impedance, indicating improved carrier separation and transport. It is mainly composed of sulfur and works synergistically with sulfur vacancies.

[0024] 4. Cu doping enhances the absorption of the material in the near-ultraviolet and visible light regions. The apparent band gap of 15% Cu-FL-MoS2 is about 1.22 eV, and the material exhibits a significant photothermal heating effect under xenon lamp irradiation.

[0025] 5. Under conditions of 180 ℃, full-spectrum irradiation by a 300 W xenon lamp, and a CO:H2 ratio of 1:1, the CO formation rate of 15% Cu-FL-MoS2 reaches 160.0 μmol•g. -1 •h -1 The CO selectivity reaches 99.0%; its CO generation rate is higher than that of undoped FL-MoS2.

[0026] 6. Comparison with light and heat factors shows that the CO generation rate under thermocatalysis alone is approximately 109.68 μmol•g. -1 •h -1 Under photothermal synergistic conditions, it was increased to 160.0 μmol•g. -1 •h -1 This indicates that light and heat have a significant synergistic promoting effect on the RWGS reaction.

[0027] 7. The catalytic activity of the selected sample remained basically stable after four cycles of testing, demonstrating good recyclability. Attached Figure Description

[0028] Figure 1 A schematic diagram of the preparation process of CTAB-assisted copper-doped few-layer MoS2 photothermal catalyst.

[0029] Figure 2 (a) shows the XRD patterns of ML-MoS2, FL-MoS2, and 15%Cu-FL-MoS2. Figure 2 (b) Figure 2 (c) Raman spectra of ML-MoS2, FL-MoS2, and 15%Cu-FL-MoS2 at different wavelengths. Figure 2 (d) shows the EPR characterization diagrams of ML-MoS2, FL-MoS2, and 15%Cu-FL-MoS2.

[0030] Figure 3 (a) is a SEM image of ML-MoS2. Figure 3 (b) and Figure 3 (c) is a SEM image of 15% Cu-FL-MoS2. Figure 3 (d) is the EDS elemental distribution map of 15%Cu-FL-MoS2, with the independent distribution maps of Cu, Mo and S shown on the right (or below).

[0031] Figure 4 (a) is a TEM image of ML-MoS2. Figure 4 (b) is a TEM image of 15% Cu-FL-MoS2. Figure 4 (c) is an HRTEM image of 15% Cu-FL-MoS2. Figure 4 (d) is a STEM-EDS element mapping composite image of 15% Cu-FL-MoS2. The leftmost part of the composite image is the ADF (annular dark field) morphology of the sample, and the right side shows the independent distribution maps of Cu, Mo and S elements respectively.

[0032] Figure 5 (a) is the XPS total spectrum of 15% Cu-FL-MoS2. Figure 5 (b) Mo 3d, Figure 5 (c)S 2p, Figure 5 (d)Cu 2p.

[0033] Figure 6 (a) Photothermal RWGS performance of Cu-FL-MoS2 at different pH values. Figure 6(b) Photothermal RWGS performance of Cu-FL-MoS2 at different reaction temperatures. Figure 6 (c) shows the photothermal RWGS performance of Cu-FL-MoS2 with different Cu doping ratios.

[0034] Figure 7 Transient photocurrent (a) and electrochemical impedance spectroscopy (b) of FL-MoS2 and Cu-FL-MoS2 with different Cu doping ratios.

[0035] Figure 8 (a) shows the UV-Vis diffuse reflectance spectra of FL-MoS2 and Cu-FL-MoS2 with different Cu doping ratios. Figure 8 (b) Band gap analysis diagrams of FL-MoS2 and 15%Cu-FL-MoS2.

[0036] Figure 9 Infrared thermal images of FL-MoS2 and 15%Cu-FL-MoS2.

[0037] Figure 10 Figure (a) shows the PDOS diagrams of MoS2 with and without sulfur vacancies, and Figure (b) shows the mechanism of the photothermal reverse water-gas shift reaction of 15% Cu-FL-MoS2. Detailed Implementation

[0038] The present invention will be further described in detail below with reference to embodiments and comparative examples. The following embodiments are only for illustrating the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art, based on their understanding of the technical solutions of the present invention, can make equivalent adjustments or substitutions to the raw material ratios, process parameters, etc., and these all fall within the scope of protection of the present invention. Reagents and equipment not specifically mentioned can be conventional commercially available products.

[0039] Example 1 Preparation of 5% Cu-FL-MoS2: 0.2 g ammonium molybdate tetrahydrate and 0.2 g thioacetamide were dissolved in 40 mL of deionized water. 0.1 g CTAB and 0.009 g copper acetate (Cu:Mo molar ratio 5%) were added. The pH of the system was adjusted to 3 with dilute hydrochloric acid. After stirring at room temperature for 30 min, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally treated at 180 °C for 20 h. After natural cooling, the sample was washed alternately with deionized water and anhydrous ethanol and centrifuged three times. The sample was then dried at 60 °C. The dried sample was ground and calcined at 400 °C for 2 h in a N2 atmosphere to obtain a 5% Cu-FL-MoS2 photothermal catalyst.

[0040] Example 2 Preparation of 10% Cu-FL-MoS2: Except for changing the amount of copper acetate added to 0.018g (Cu:Mo molar ratio of 10%), the other operations were the same as in Example 1, and a 10% Cu-FL-MoS2 photothermal catalyst was obtained.

[0041] Example 3 Preparation of 15% Cu-FL-MoS2 Except for changing the amount of copper acetate added to 0.027g (Cu:Mo molar ratio of 15%), the other operations were the same as in Example 1, and a 15% Cu-FL-MoS2 photothermal catalyst was obtained.

[0042] Example 4 Preparation of 20% Cu-FL-MoS2 Except for changing the amount of copper acetate added to 0.036g (Cu:Mo molar ratio of 20%), the other operations were the same as in Example 1, and a 20% Cu-FL-MoS2 photothermal catalyst was obtained.

[0043] Comparative Example 1 Preparation of FL-MoS2: Except for the absence of copper acetate, the operation was the same as in Example 1, and the FL-MoS2 control sample was obtained.

[0044] Comparative Example 2 Preparation of ML-MoS2 Except for the absence of CTAB and copper acetate, the other operations were the same as in Example 1, and a multilayer MoS2 (ML-MoS2) control sample was obtained.

[0045] I. Structural Characterization and Performance Evaluation 1. Characterization of phases and defects X-ray diffraction (XRD), Raman spectroscopy, and electron paramagnetic resonance (EPR) were used to characterize ML-MoS2, FL-MoS2, and 15%Cu-FL-MoS2, respectively. The results are as follows: Figure 2 As shown.

[0046] XRD results showed that ML-MoS2, FL-MoS2, and 15%Cu-FL-MoS2 all exhibited the (002), (100), and (110) characteristic diffraction peaks of 2H phase MoS2. Compared with ML-MoS2, the intensity of the (002) diffraction peak was significantly weakened after the introduction of CTAB, indicating that the addition of CTAB effectively suppressed the stacking growth of MoS2 along the c-axis, which is beneficial to the formation of few-layer structures. The (100) crystal plane diffraction peak shifted slightly after Cu doping, indicating that the introduction of Cu modulates the local lattice structure of MoS2.

[0047] In the Raman spectra, all samples exhibited characteristic vibrational peaks of 2H-MoS2. After Cu doping and CTAB modulation, the characteristic peaks shifted slightly, and D and G bands associated with residual carbon were observed.

[0048] EPR results showed that sulfur vacancy defects existed in the samples after hydrothermal treatment and calcination; the sulfur vacancy signal was enhanced after CTAB modulation, and Cu doping further changed the defect center characteristics, indicating that there is a synergistic defect regulation between Cu species and sulfur vacancies.

[0049] 2. Microscopic morphology characterization The morphology of ML-MoS2 and 15% Cu-FL-MoS2 was characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results are as follows: Figure 3 and Figure 4 As shown.

[0050] Figure 3 SEM and EDS analysis: Figure 3 (a) shows that ML-MoS2 exhibits a distinct multilayered stacked morphology, with relatively large particle size and a dense surface. This is due to the natural stacking growth of MoS2 along the c-axis without the addition of CTAB. In contrast, Figure 3 In (b) and (c), 15% Cu-FL-MoS2 exhibits a thinner layered structure with more uniform lamellae and abundant edges and defect sites on the surface, indicating that CTAB, as a cationic surfactant, forms micelles in the solution and effectively suppresses the interlayer stacking of MoS2 through electrostatic interaction and steric hindrance effect. Figure 3 (d) is the EDS elemental mapping combination diagram of 15% Cu-FL-MoS2. This combination diagram contains the independent distribution diagrams of Cu, Mo and S elements. It can be seen from the figure that the Cu element is highly overlapping and uniform in spatial distribution with Mo and S elements. There is no obvious Cu agglomeration phenomenon, indicating that Cu species have been uniformly dispersed and doped into the MoS2 structure.

[0051] Figure 4 TEM and HRTEM analyses: Figure 4 (a) is a TEM image of ML-MoS2, in which approximately 6 to 8 layers of stacking can be clearly observed along the (002) direction. Figure 4 (b) is a TEM image of 15% Cu-FL-MoS2, with an average of about 2.6 layers, mainly 2 to 4 layers, which further confirms the effect of CTAB on the regulation of few-layer structures. Figure 4 (c) The HRTEM image shows clear lattice fringes with a lattice spacing of about 0.62 nm, corresponding to the (002) crystal plane of 2H-MoS2. No lattice fringes of independent crystal phases such as CuO or CuS were found, indicating that Cu species exist in the MoS2 structure in the form of atomic dispersion or small clusters. Figure 4 (d) is a STEM-EDS elemental mapping composite image of 15% Cu-FL-MoS2. The leftmost image shows the ADF (annular dark field) morphology of the sample, and the rightmost images show the independent distribution maps of Cu, Mo, and S. The independent mapping maps show that Cu, Mo, and S have a highly consistent and uniform spatial distribution, further confirming that Cu species have been uniformly dispersed and successfully doped into the MoS2 structure, consistent with the SEM-EDS results.

[0052] 3. Characterization of the chemical state of elements X-ray photoelectron spectroscopy (XPS) was used to characterize 15% Cu-FL-MoS2, and the results are as follows: Figure 5 As shown.

[0053] XPS full spectrum showed the presence of Cu, Mo, and S elements in 15% Cu-FL-MoS2. Mo was the dominant element observed in the 3d spectrum. 4+ Related peaks, and a small amount of Mo is present. 6+ This indicates that Mo in the sample mainly exists in the +4 oxidation state and is partially oxidized. The S 2p spectrum shows S 2- Characteristic peaks. The Cu 2p spectrum shows characteristic peaks at approximately 932.73 eV and 952.76 eV, indicating that Cu in the sample exists in a low valence state. + Species-based, rather than Cu 2+ This result demonstrates that the method of the present invention successfully introduces Cu into the MoS2 lattice in a low valence state.

[0054] 4. Photoelectrochemical performance testing In a 0.5 M Na₂SO₄ solution, using the prepared catalyst as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode, transient photocurrent and electrochemical impedance spectroscopy (EIS) tests were performed under 300 W xenon lamp irradiation. The results are as follows: Figure 7 As shown.

[0055] Figure 7 (a) Transient photocurrent response: The photocurrent density of Cu-FL-MoS2 with different Cu doping ratios was higher than that of undoped FL-MoS2, indicating that Cu doping is beneficial to the excitation of photogenerated carriers. Among them, 15% Cu-FL-MoS2 had the strongest photocurrent response, indicating that a moderate Cu doping amount is most conducive to the generation and separation of carriers. The photocurrent spiked in the early stage of illumination and then decayed rapidly and tended to stabilize. This is a typical photogenerated carrier transport behavior of semiconductor materials. The spike comes from transient carrier accumulation, and the steady state reflects the continuous carrier generation-transport balance.

[0056] Figure 7(b) Electrochemical impedance spectroscopy: In the Nyquist plot, the radius of the arc directly reflects the magnitude of the charge transfer resistance. FL-MoS2 has the largest arc radius, indicating its high charge transfer resistance; the arc radius decreases significantly after Cu doping, with 15% Cu-FL-MoS2 having the smallest arc radius, indicating that appropriate Cu doping can effectively reduce charge transfer resistance and improve the transport efficiency of charge carriers inside the material and at the interface. This result is consistent with the transient photocurrent test results, jointly confirming the promoting effect of Cu doping on charge carrier dynamics.

[0057] 5. Optical performance and photothermal effect testing UV-Vis diffuse reflectance spectroscopy was performed on FL-MoS2 and Cu-FL-MoS2 with different Cu doping ratios. The results are as follows: Figure 8 As shown.

[0058] Figure 8 (a) UV-Vis diffuse reflectance spectra: All samples exhibited strong absorption in the UV region (200-400 nm). After Cu doping, the absorption intensity of the materials in the near-UV and visible regions (400-700 nm) was significantly enhanced, and the absorption in the visible region gradually increased with increasing Cu doping concentration. The enhanced absorption is attributed to the impurity energy levels formed by the introduction of Cu species and the electronic interactions between Cu 3d orbitals and Mo 4d / S 3p orbitals.

[0059] Figure 8 (b) Bandgap analysis: Calculated using the Kubelka-Munk function, the apparent bandgap of FL-MoS2 is approximately 1.39 eV, while that of 15% Cu-FL-MoS2 is approximately 1.22 eV, indicating a significant narrowing of the bandgap. This reduction in bandgap expands the photoresponse range of the material, facilitating the generation of photogenerated carriers using more visible light, thereby enhancing photocatalytic activity and photothermal conversion efficiency.

[0060] The surface temperature changes of FL-MoS2 and 15%Cu-FL-MoS2 under 300 W xenon lamp irradiation with time were recorded using an infrared thermal imager. The results are as follows: Figure 9 As shown, the surface temperature of both materials increases with irradiation time under illumination, exhibiting a significant photothermal effect. FL-MoS2 reaches a surface temperature of 44.3℃ after approximately 40 seconds of illumination, while 15% Cu-FL-MoS2 shows a faster photothermal temperature rise and a higher equilibrium temperature, ultimately reaching 45.2℃. The enhanced photothermal conversion capability of the materials after Cu doping is attributed to the lower valence state of Cu. + The introduction of species and sulfur vacancies reduces the band gap and thermal radiation loss of the material, promoting the conversion of light energy into heat energy. This photothermal effect can increase the catalyst surface temperature in the photothermal RWGS reaction, thus promoting surface reaction kinetics.

[0061] II. Performance Evaluation of Photothermal Reverse Water-Gas Shift Reaction 1. Reaction conditions and performance testing The prepared catalyst was used in a photothermal CO2 hydrogenation reaction. The reaction was carried out in a fixed-bed continuous flow reactor with a catalyst loading of 50 mg, a reaction pressure of 0.2 MPa, a reaction gas composition of CO2:H2 = 1:1 (volume ratio), and a total flow rate of 20 mL·min. -1 The light source was a 300 W xenon lamp with a full spectrum, and the reaction temperature was 140–180 °C. The products were analyzed online by gas chromatography.

[0062] 2. pH condition optimization 15% Cu-FL-MoS2 was prepared according to the method in Example 3 under different pH conditions (pH=2, 3, 4), and its photothermal RWGS performance was evaluated under full-spectrum illumination at 180℃. The results are as follows: Figure 6 As shown in (a), the catalyst prepared at pH=3 has the highest CO generation rate, therefore, the subsequent examples were all prepared at pH=3.

[0063] 3. Performance comparison of different Cu doping ratios The photothermal RWGS performance of FL-MoS2 and Cu-FL-MoS2 prepared in Examples 1-4 with different Cu doping ratios was evaluated under full-spectrum illumination at 180 °C. The results are as follows: Figure 6 As shown in (c).

[0064] With increasing Cu doping concentration, the CO formation rate initially increases and then decreases. 15% Cu-FL-MoS2 exhibits the best performance, with a CO formation rate of 160.0 μmol•g. -1 •h -1 The CO selectivity was 99.0%, significantly better than undoped FL-MoS2. This indicates that appropriate Cu doping (15%) can achieve Cu... + Optimal synergistic matching between species and sulfur vacancies leads to a highly efficient active structure; however, excessive Cu doping (20%) causes Cu species to aggregate on the MoS2 surface, covering active sites and potentially disrupting the electronic structure of sulfur vacancies, thus reducing catalytic performance. Furthermore, appropriate Cu doping enhances light absorption and improves carrier separation efficiency, while excessive Cu introduces deep-level defects that may become electron-hole recombination centers, reducing quantum efficiency.

[0065] 4. Verification of photothermal synergistic effect To verify the promoting effect of light on the reaction, experiments with both light and heat (300 W xenon lamp full-spectrum irradiation + external heating) were conducted at different reaction temperatures (140℃, 160℃, and 180℃). The results are as follows: Figure 6 As shown in (b).

[0066] The results showed that the CO formation rates at 140 ℃, 160 ℃, and 180 ℃ were approximately 5, 90, and 160 μmol•g, respectively. -1 •h -1 The CO selectivity was above 90%. The CO formation rate increased significantly with increasing temperature, indicating that the reaction was thermally driven. At 180 °C, the CO formation rate under photothermal synergistic conditions was 160.0 μmol•g. -1 •h -1 The result was significantly higher than the approximately 109.68 μmol•g under the same temperature and thermocatalytic conditions alone. -1 •h -1 This indicates a significant synergistic promoting effect between light and heat. Photogenerated charge carriers can participate in the activation process of CO2 and H2, lowering the reaction activation energy, while the photothermal effect can increase the catalyst surface temperature and accelerate surface reaction kinetics. The synergistic effect of the two effectively enhances the rate of the RWGS reaction.

[0067] In addition, under optimized reaction conditions (180 °C, 300 W xenon lamp full-spectrum irradiation, CO2:H2=1:1), the 15%Cu-FL-MoS2 was subjected to four cycles of stability testing. Each cycle lasted 4 h, and the catalyst was purged at the reaction temperature under N2 atmosphere for 30 min between cycles before entering the next cycle. The results showed that after four cycles, neither the CO generation rate nor the CO selectivity decreased significantly, indicating that the 15%Cu-FL-MoS2 prepared in this invention has good cycling performance and structural stability.

[0068] 5. Photothermal RWGS Reaction Mechanism Analysis Based on the above characterization and performance test results, the mechanism of action of the Cu-FL-MoS2 photothermal catalyst prepared in this invention in the reverse water-gas shift reaction can be summarized as follows (e.g.) Figure 10 (as shown) First, the introduction of CTAB effectively reduces the number of layers in MoS2 (from 6-8 layers to 2-4 layers), exposing more edge active sites and basal defect sites, which is beneficial for the adsorption and diffusion of reactant molecules. Simultaneously, the hydrothermal reaction and subsequent calcination under nitrogen atmosphere introduce a suitable amount of sulfur vacancy defects into MoS2. For example... Figure 10 As shown in (a), the projected density of states (PDOS) comparison shows that sulfur vacancies introduce new defect states near the Fermi level, which is beneficial for electron transfer and chemisorption of CO2 and H2 molecules on the catalyst surface.

[0069] Secondly, Cu species exist in low valence state Cu. +The form is uniformly dispersed in few-layer MoS2 and / or on its surface. Sulfur vacancies induce electronic rearrangement of adjacent Mo sites, making them more conducive to interaction with CO2 and H2; Cu + A synergistic catalytic active structure is formed between the species and the sulfur vacancy. This synergy facilitates the activation of reactant molecules and promotes the desorption of adsorbed CO intermediates, thereby suppressing excessive hydrogenation side reactions. This explains why 15% Cu-FL-MoS2 can simultaneously achieve a high CO rate (160.0 μmol•g). -1 •h -1 The reason for its high CO selectivity (99.0%).

[0070] Third, Cu doping improves the light absorption performance of MoS2 (the band gap is narrowed from 1.39 eV to about 1.22 eV) and its photothermal conversion capability. Figure 9 Infrared thermal imaging confirmed that the catalyst surface temperature significantly increased under illumination, which is beneficial for improving surface reaction kinetics. Simultaneously, Cu doping promoted the separation and transport of photogenerated carriers. Figure 7 (With enhanced transient photocurrent and reduced charge transfer resistance), photogenerated electrons can participate in the activation processes of CO2 and H2. Figure 10 (b) shows the complete mechanism diagram, which fully presents the above process, including the synergistic mechanism of Cu species, sulfur vacancies and photothermal effects on the activation of CO2 and H2.

[0071] In summary, this invention achieves few-layer 2H-MoS2 and low-valence Cu through a synergistic strategy of CTAB-assisted morphology control, Cu doping, and sulfur vacancy defect engineering. + The synchronous construction of species and sulfur vacancies, through their synergistic effect, significantly enhances the catalytic activity and CO selectivity of the photothermal reverse water-gas shift reaction.

Claims

1. A copper-doped few-layer MoS2 photothermal catalyst, characterized in that, The photothermal catalyst is mainly composed of 2H phase few-layer MoS2, which contains sulfur vacancies. Cu species are dispersed in the few-layer MoS2 and / or on its surface, and at least some of the Cu species are low-valence Cu. + The Cu species and the sulfur vacancy constitute a synergistic catalytically active structure.

2. The copper-doped few-layer MoS2 photothermal catalyst according to claim 1, characterized in that, The number of layers in the few-layer MoS2 is 2 to 4.

3. The copper-doped few-layer MoS2 photothermal catalyst according to claim 1, characterized in that, The molar ratio of Cu to Mo in the photothermal catalyst is 5% to 20%.

4. The copper-doped few-layer MoS2 photothermal catalyst according to claim 3, characterized in that, The molar ratio of Cu to Mo is 15%.

5. A method for preparing a copper-doped few-layer MoS2 photothermal catalyst as described in any one of claims 1-4, characterized in that, Includes the following steps: Ammonium molybdate tetrahydrate and thioacetamide were dissolved in deionized water at a mass ratio of 1:

1. Hexadecyltrimethylammonium bromide and copper acetate were added to adjust the pH of the system to 2-4. After mixing, the mixture was subjected to a hydrothermal reaction at 160-200℃ for 16-24 h. The hydrothermal product was washed, dried, and calcined at 350-450℃ for 1-3 h under a nitrogen atmosphere to obtain the copper-doped few-layer MoS2 photothermal catalyst. The concentration of hexadecyltrimethylammonium bromide added to the reaction system is 1~5 g / L, and the molar ratio of Cu to Mo is 5%~20%.

6. The preparation method according to claim 5, characterized in that, The molar ratio of Cu to Mo is 15%.

7. The application of the copper-doped few-layer MoS2 photothermal catalyst as described in any one of claims 1-4 in the photothermal reverse water-gas shift reaction, characterized in that, Under the synergistic effect of light and heat, CO2 reacts with H2 to produce CO and H2O.

8. The application according to claim 7, characterized in that, The conditions for the photothermal reverse water-gas conversion reaction are: reaction temperature 140~180℃, reaction pressure 0.2 MPa, CO2 to H2 volume ratio in the reaction gas 1:1, and the light source is a 300 W xenon lamp full-spectrum light source.